SAKU-BUMNag: Sistem Aplikasi Keuangan Sederhana untuk Badan Usaha Milik Nagari - Sururi Awwali Fitri; Friyatmi Friyatmi (Universitas Negeri Padang, 2023)
BUMNag is an important factor in the village's economic development. Preparing financial reports is a challenge that many BUMNag managers face due to human resource shortages. This study aims to develop a valid SAKU-BUMNag as a simple financial system for BUMNag's financial management. It is a research development that employs the 4D model which consists of the define, design, develop, and disseminate stages. data was collected using questionnaires and validation sheets. Expert judgment is used to evaluate product validity, which is quantified using descriptive statistics. The findings indicate that SAKU-BUMNag is a feasible tool for assisting the financial systems of nagari-owned enterprises. It is user-friendly, which makes it easier for BUMNag managers to produce financial information that meets the relevant accounting requirements.